THE INFLUENCE OF ORGANIZATIONAL CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE - Tutik Winarsih; Arif Hidayat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The main purpose of the study is to investigate the impact of "X" Company's culture and motivation on its employees' performance. 30 employees of "X" Company were the subjects of this investigation. Quantitative approaches were used in this study. A questionnaire was utilized to gather the information. The SPSS version 22 program for Windows was utilized to do the multiple linear regression data analysis in this study. As shown in the findings of this study, both organizational culture and employee motivation have a positive and significant impact on employee performance. A further finding of the R2 indicates that 92.4 % of the factors of employee performance is , while the remaining 7.6 % is due to factors beyond the scope of this study Keywords: Organizational Culture, Motivation, Employee Performance